PENGGUNAAN LIMBAH SERBUK BESI SEBAGAI CAMPURAN AGREGAT HALUS PADA ASPHALT CONCRETE-WEARING COURSE (AC-WC) - Umma Chintya Devi; Nur Azizah Affandy (JMTS: Jurnal Mitra Teknik Sipil, 2021)
As time goes by, roads are easily damaged due to the large number of transportation that passes. For this reason, the development of new findings is continuously being made to improve the strength of the road layers. In this study, iron powder waste was used because from a physical perspective, iron powder is very similar to fine aggregate. In this study, iron powder waste was used as an additive for fine aggregate with a content of 0%, 4%, 4.5%, 5% by weight of fine aggregate. The purpose of this study was to determine the effect of iron powder waste on Marshall Properties parameters. This study uses the Marshall Properties test method consisting of stability (kg), VIM (%), VMA (%), VFA (%), Flow and Marshall Quotien. For the best results from the comparison of asphalt with 0% content and asphalt with added ingredients, namely stability 0% yield 997 kg and 4% yield 788 kg, Flow 0% yield 3.17 mm and 4% yield 3.33 mm, VMA 0% yield 17.29% and 4% yield 15.84%, VIM 0% yield 4.14% and 4% yield 2.46%, VFA 0% yield 74.97% and 5% yield 88.76% and MQ 0% yields of 309.31 kg / mm and 5% yields of 246.80 kg / mm. From here it can be seen that the level of 4% more shows the best results and meets the standards. ABSTRAKSeiring berkembangnya jaman, jalan mudah sekali mengalami kerusakan karena banyaknya transportasi yang melintas. Untuk itu, pengembangan temuan baru terus dilakukan untuk memperbaiki kekuatan lapisan jalan. Dalam penelitian ini digunakan limbah serbuk besi karena dari segi fisik, serbuk besi sangat mirip dengan agregat halus. Dalam penelitian ini, limbah serbuk besi digunakan untuk bahan tambah agregat halus dengan kadar 0%, 4%, 4.5%, 5% dari berat agregat halus. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh dari limbah serbuk besi terhadap parameter Marshall Properties. Penelitian ini menggunakan metode pengujian Marshall Properties yang terdiri dari Stabilitas (kg), VIM (%), VMA (%), VFA (%), Flow dan Marshall Quotien. Untuk hasil terbaik dari perbandingan aspal dengan kadar 0% dan aspal dengan bahan tambah yaitu stabilitas 0% hasil 997 kg dan 4% hasil 788 kg, Flow 0% hasil 3,17 mm dan 4% hasil   3,33 mm, VMA 0% hasil 17,29% dan 4% hasil 15,84%, VIM 0% hasil 4,14% dan 4% hasil 2,46%, VFA 0% hasil 74,97% dan 5% hasil 88,76% dan MQ 0% hasil 309,31 kg/mm dan 5% hasil 246,80 kg/mm. Dari sini dapat dilihat kadar 4% lebih banyak menunjukan hasil terbaik dan hampir memenuhi standart.